2013
DOI: 10.1002/chem.201301521
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Organotin‐Chalcogenide Complexes That Exhibit Defect Heterocubane Scaffolds: Formation, Synthesis, and Characterization

Abstract: The synthesis of new functionalized organotin-chalcogenide complexes was achieved by systematic optimization of the reaction conditions. The structures of compounds [(R(1, 2) Sn)3 S4 Cl] (1, 2), [((R(2) Sn)2 SnS4 )2 (μ-S)2 ] (3), [(R(1, 2) Sn)3 Se4 ][SnCl3 ] (4, 5), and [Li(thf)n ][(R(3) Sn)(HR(3) Sn)2 Se4 Cl] (6), in which R(1) =CMe2 CH2 C(O)Me, R(2) =CMe2 CH2 C(NNH2 )Me, and R(3) =CH2 CH2 COO, are based on defect heterocubane scaffolds, as shown by X-ray diffraction, (119) Sn NMR spectroscopy, and ESI mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 65 publications
(33 reference statements)
5
48
2
Order By: Relevance
“…The formation of the ionic compounds C or D from the neutral compounds 3 or 6 , and their subsequent co‐crystallization, can be attributed to a (partial) decomposition of the neutral species in solution with reductive formation of the [Sn II Cl 3 ] − counterion and oxidation of the ligand R 1 , as discussed previously …”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…The formation of the ionic compounds C or D from the neutral compounds 3 or 6 , and their subsequent co‐crystallization, can be attributed to a (partial) decomposition of the neutral species in solution with reductive formation of the [Sn II Cl 3 ] − counterion and oxidation of the ligand R 1 , as discussed previously …”
Section: Resultsmentioning
confidence: 69%
“…The first neutral DC tin sulfide cluster, [(SnR 1 ) 3 S 4 Cl] (R 1 =CMe 2 CH 2 C(O)Me), was obtained by reaction of R 1 SnCl 3 (A) with (SiMe 3 ) 2 S . Investigations of this system have shown that different cluster topologies can be selectively and systematically obtained by tuning the Sn/S ratio of the corresponding precursor mixture, thereby initiating a stepwise reaction cascade between R 1 SnCl 3 and S(SiMe 3 ) 2 with the concomitant release of Me 3 SiCl.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as this generally allows for further extension of the cluster surface and attachment to solid substrates, one of our current aims is the synthesis and thorough investigation of metal chalcogenide clusters that comprise ligands with functional groups. [3][4][5][6][7][8] For accessing ternary, organo-functionalized chalcogenide clusters, in which main group (semi-)metal atoms are combined with transition metal atoms for an even finer tunable electronic situation, the use of organotetrel chalcogenide clusters like [(R 1 T) 3 E 4 Cl] or [(R 1 T) 4 E 6 ] [R 1 = CMe 2 CH 2 C(O)Me, T = Ge, Sn; E = S, Se, Te] has proven an efficient and versatile way. [5,[9][10][11][12][13][14] 3 is the first compound based on a [Pd 2 SnSe 2 ] moiety, which furthermore exhibits a functional organic group at the tin atom.…”
Section: Introductionmentioning
confidence: 99%